Penyuluhan Seni Gamelan Dukuh Kadireso (Jurnal Pengabdian Seni, 2020)
Berawal dari pelaksanaan KKN, penulis menjumpai dan merintis terbentuknya kelompok gamelan di Dukuh Kadireso. Pada pengabdian ini, penulis berfokus pada kurangnya apresiasi pada warisan budaya dan kembali melakukan penyuluhan dengan metode pembelajaran langsung: teknik tiap ricikan, membaca notasi, dan praktik bersama. Materi yang diberikan diharapkan dapat membantu konsistensi kelompok gamelan ini untuk dapat beraktivitas secara mandiri. Hasil dari pengabdian ini adalah tercapainya penguasaan materi pada Gangsaran dan Lancaran "Ayo Kanca Nabuh Gamelan" serta terbentuknya komunitas diskusi kesenian di Karang Taruna Dukuh Kadireso.The writer is exposed to the community of Kadireso village started from an undergraduate field program, in which the writer met and started a gamelan (traditional Javanese music instrument) group. In this opportunity, the writer focuses in the community’s lack of appreciation for the cultural heritage and reintroduces the gamelan workshop through an intensive teaching sessions: technique in each ricikan (stanza), reading music notes, and communal practices. The material given are hoped to be able to lead them into consistency and to engage in the activity independently. Results of this workshop shows that the group is now able to master the beginner drill of Gangsaran and Lancaran: “Ayo KancaNabuh Gamelan” and is able to solidify the arts discussion community in Kadireso village youth community.